Poetycki realizm dziecięcego świata, czyli małe tragedie w szkolnych etiudach Doroty Kędzierzawskiej - Dzieniszewska, Karolina (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
A consistent style in Dorota Kędzierzawska’s films has been clearly visible since her university works, which were influenced by cinematic Polish tendencies from the 1970s and 1980s. The director was interested in making deep insights into the child’s world and taking the perpective of her main characters. The spirit of the visual element does not minimalise the realism of the filmed world. What is more, the limited role of speaking allows cinematic techniques of expression to develop. Kędzierzawska has always been fascinated by young people and their problems and life experiences.